Patron's Day 2002 (Institutional Knowledge at Singapore Management University, 2002)
Singapore Management University Patron and Singapore President S R Nathan (centre) and SMU students at Patron’s Day 2002. President Nathan presented awards to students who showed excellence in sports, cultural and social activities. The event was held at SMU's Bukit Timah campus on 11 January 2002.